MODEL OF PROMOTING WELL-BEING OF ETHNIC COMMUNITY OF MONKS IN RATCHABURI PROVINCE - Visuddho, Phrasamu Wasin; (Kampol Kunungkaro), Phraudomsittinayok; Srirat, Nigorn (Journal of MCU Social Science Review, 2022)
Objectives of this research were to study the general conditions, process and present the model of the promoting well-being of ethnic community of monks in Ratchaburi Province. Methodology was the qualitative research methodology for collecting field data from in-depth interviews with 25 key informants by using a structured interview script with a content validity index (S-CVI) of 1.00 as a tool for data collection and Focus group discussion with 8 experts by analyzing the data with contextual content analysis techniques. The findings of this research as following; 1. The most of monks who lived in the area or had been in the area for a long time, so they knew and realized the health problems of the ethnic community very well. 2. The monks had implemented the keeping 5 precepts village project and the health promotion temple project that supported the promotion of well-being for the people that covered physical, mental, social and intellectual, etc., in terms of Samadhi, monks encouraged people to control their emotions in their lives in accordance with the principles of mental well-being, etc. and Pañña, monks had trained people in Vipassana meditation by aiming to raise their intellectual level to serve as the core for the development of holistic health. 3. The model of action to solve the health problems of ethnic people by using strengths to drive opportunities, using opportunities to mitigate weaknesses, using strengths to overcome obstacles and fix weaknesses while avoiding obstacles by covering health promotion in four aspects.